Students’ Awareness of Drug Abuse as a Basis for Guidance and Counseling Interventions: A Rasch Measurement Analysis - Pini Pitria; Yeni Karneli; Rezki Hariko; Zadrian Ardi (Jurnal Konseling dan Pendidikan, 2026)
Drug abuse among students remains a serious challenge that requires school-based preventive efforts. One important factor in prevention is students’ awareness of the dangers of drugs. However, previous studies have generally relied on conventional statistical approaches that are limited in mapping variations in students’ awareness levels. This study aimed to analyze students’ awareness of drug abuse as a basis for developing guidance and counseling interventions using the Rasch Measurement approach. A quantitative survey design was employed involving 582 secondary school students selected through proportionate stratified random sampling. Data were analyzed using the Rasch Rating Scale Model through Winsteps software. The findings showed that students’ awareness was generally at a moderate to good level, although a subgroup with low awareness still required special attention. The analysis also revealed heterogeneity in students’ awareness levels, indicating that students should not be treated as a homogeneous group. These findings suggest that school-based drug prevention interventions should be designed according to students’ needs profiles through more targeted guidance and counseling services, such as psychoeducation, classroom guidance, group counseling, and individual mentoring. This study provides a practical contribution by offering a data-driven assessment basis for developing preventive school services.